Legal Protection of the Pebatinan Air Suluh di Laut Indigenous Community Against Land Issues with PT. Gandaerah Hendana in Kerumutan District - Olfi Andari; Zulherman Idris; Erlina (International Conference On Law And Social Sciences, 2024)
The presence of indigenous communities has long been a social reality. Its existence has been around for hundreds of years, characterized by various human groups with living arrangements in a certain territory. Recognition and protection of indigenous peoples, until now there has been a long debate regarding the pattern of recognition and protection. Legal protection is a development of the concept of recognition and protection of Human Rights (HAM). Meanwhile, the direction of the concept of recognition and protection of human rights is the existence of restrictions and placing obligations on society and the government. The main problem in this research is, how is the legal protection of the Pebatinan Air Suluh di laut Indigenous Community against land problems with PT. Gandaerah Hendana in Kerumutan sub-district and what are the factors causing the land problems of the Pebatinan Air Suluh di laut indigenous community with PT. Gandaerah Hendana. The research method used is sociological juridical with direct primary data collection in the field. The method used is a descriptive research method carried out by interviewing predetermined respondents. From the research results, it can be concluded: that recognition and protection of legal communities is carried out through three stages, the first is identification of customary legal communities, verification and validation of traditional legal communities, but it is necessary to know that the position of traditional institutions in Pelalawan Regency, especially customary law communities in Kerumutan District, has not been strengthened. with Regional Regulations so that it is necessary to form Regional Regulations which regulate specifically the legal recognition and protection of customary law communities on ulayat land. What causes the land problems of the Pebatinan Air Suluh di laut customary law community, is the disorganized administration in the past, unclear control and ownership, claims/indications that the rights of one of the parties are not fulfilled. Therefore, it is necessary to handle and resolve conflicts which aim to provide legal certainty regarding control, ownership, use and utilization of the Pebatinan Air Suluh dilaut customary land.